Role of lncRNAs in acute pancreatitis: pathogenesis, diagnosis, and therapy - Deng, Jie; Song, Ziying; Li, Xiaolan; Shi, Huiqing; Huang, Shangqing; Tang, Lijun (Frontiers in Genetics, 2023)
Acute pancreatitis (AP) is one of the common acute abdominal disease characterized by the injury and inflammatory disorder of the pancreas with complicated pathological mechanisms. Long non-coding RNAs (lncRNAs) have emerged the important role in various physiological and pathological processes in humans, and their potential as the biomarkers of diagnosis and therapeutic targets in various diseases. Recently, accumulating evidence has shown that the significant alterations in expression of lncRNAs, which are involved in the pathogenesis of AP, such as premature trypsinogen activation, impaired autophagy, inflammatory response and acinar cells death. Moreover, lncRNAs can be the direct target of AP treatment and show the potential as the biomarkers for the diagnosis. Thus, in this review, we focus on the role of lncRNAs in pathogenesis, diagnosis and therapy of AP and emphasize the future directions to study lncRNAs in AP, providing a new insight into understanding cellular and molecular mechanisms of AP and seeking for novel biomarkers for the diagnosis and therapeutic targets to improve clinical management in the future.